Cardiac Intravoxel Incoherent Motion Diffusion‐Weighted Magnetic Resonance Imaging With T1 Mapping to Assess Myocardial Perfusion and Fibrosis in Systemic Sclerosis: Association With Cardiac Events From a Prospective Cohort Study. Issue 9 (2nd August 2020) - Terrier, Benjamin; Dechartres, Agnès; Gouya, Hervé; Ben Arfi, Moncef; Bérézne, Alice; Régent, Alexis; Dunogué, Bertrand; London, Jonathan; Cohen, Pascal; Guillevin, Loïc; Le Jeunne, Claire; Legmann, Paul; et al.
Abstract : Objective: Myocardial involvement may occur during systemic sclerosis (SSc) and can lead to impaired myocardial contraction and/or arrhythmia. Cardiac magnetic resonance imaging (MRI) is used for noninvasive characterization of the myocardium. The aim of this study was to evaluate the utility of cardiac MRI with intravoxel incoherent motion (IVIM) diffusion‐weighted imaging (DWI) and longitudinal relaxation time (T1) sequence mapping for assessment of myocardial microvascular and interstitium impairment in SSc. Methods: In this single‐center prospective cohort study, 40 consecutive patients with SSc and 20 healthy controls were assessed by cardiac MRI with IVIM DWI and T1 mapping sequences on a 3T scanning system. Images were analyzed independently by 2 assessors, and Bland‐Altman plots were used to assess interreader concordance and reproducibility. Characteristics of the patients were compared according to quartiles of T1 and perfusion fraction (f‐coefficient) values, using exact Cochran‐Ermitage trend tests for qualitative variables and analysis of variance for quantitative variables. Kaplan‐Meier cardiac events–free survival curves were plotted and compared with a log‐rank test for trend. Results: T1 values were higher in SSc patients than in healthy controls, and were higher in the diffuse cutaneous SSc (dcSSc) subset ( P  = 0.02). Higher T1 values were associated with the immunologic pattern seen in patients with the dcSSc form ( P  = 0.0001), a higher modified Rodnan skin thickness score (MRSS) ( P  = 0.003), and a higher frequency of interstitial lung disease ( P  = 0.03). Moreover, higher T1 values were correlated with higher MRSS scores (r = +0.32, P  = 0.04) and reduced forced vital capacity (r = −0.34, P  = 0.048), and tended to be correlated with reduced total lung capacity (r = −0.30, P  = 0.07). Lower f‐coefficient values, as a measure of decreased tissue perfusion, were associated with less frequent use of vasodilators ( P  = 0.02 for angiotensin‐converting enzyme inhibitors and P  = 0.06 for calcium‐channel blockers) and more frequent use of glucocorticoids ( P  = 0.02). The f‐coefficients were inversely correlated with the T1 values (r = −0.31, P  = 0.02). Furthermore, higher T1 values were associated with higher incidence of cardiac events (log‐rank test for trend P  = 0.03). Conclusion: Increased T1 values, potentially suggesting microscopic fibrosis, were observed more frequently in patients with dcSSc, and higher T1 values were associated with interstitial lung disease and more frequent cardiac events during follow‐up. The results of this study show that cardiac MRI with T1 mapping sequences and IVIM DWI may be useful in assessing myocardial involvement in patients with SSc.